Fluor Consentration After Fissured Sealent As The Time Observed With Fuji Vii As Glass Ionomer Cement - Endah Aryati Eko Ningtyas; Tri Wiyatini; Aning Susilowati (Poltekkes Kemenkes Semarang, 2012)
The Aims of this research was to know the differenrence of fluor content in saliva and plaque after was fissured sealent with Fuji VII. Research approach was experimental with Post test only group design. Research subject were twenty two children at 9-10 years old. Fluoride counted on subject at before fissured sealent at 1 days and after fissured sealent at 7,14,40 days. Every observated time, The data’s of fluor was measured using Spektrofotometri DR 2000. Then data’s were analyzed by using Two Way repeated Anova test. The result showed there was a difference of fluor amount at saliva and plaque after fissured sealent at every time observation (Two Way repeated Anova significanve). There was highest realesed fluor amount at 7days after fissured sealent and there was lower realesed fluor amount toward at 14,40 days. The Highest amount of fluor at saliva compared to plaque.